Characterization of a Fluorinated Ferroelectric Liquid Crystal by Molecular Optimization Electro-Optic Study and SAXS - Goswami, Debarghya (Journal of Scientific Research, 2025)
In this work a fluorinated ferroelectric liquid crystal has been characterized by molecular optimization, electro-optic study and small angle x-ray scattering (SAXS) to investigate its applicability for display and NLO applications and also to inculcate the relation between its structural conformation and bulk property. The optimized molecular structure of the compound was simulated and different molecular properties were calculated by means of quantum calculations (Hartree-Fock method). The phase behavior of the compound was studied by Polarized optical microscopy (POM) study. The Polarizing optical microscopy revealed a broad spectrum of ferroelectric SmC* phase and a short range SmA* phase in the compound. The electrical response time was measured and was found to be in micro second range. The layer spacing and the tilt angles of the molecules in SmC* phase was measured using SAXS. For its large thermal span of ferroelectric SmC* phase and response time in microsecond range the compound found to be potentially useful for formulating one ferroelectric room temperature liquid crystal mixture, appropriate for display applications.